The Obstacles Faced by the English Teacher in Assisting Students to Win Storytelling Contest at Methodist Senior High School, Banda Aceh - Mulyadi Syahputra; Bustami Usman; Bukhari Daud (English Education Journal, 2018)
The aims of this research were to find out the teacher’s obstacles in preparing their students to win storytelling contest. This study was designed using the descriptive qualitative method. The results of the study were collected through interviewing the teacher in Methodist Senior High School who was purposely selected by their achievement in preparing the students in some storytelling contests. The conclusion of the study that the teacher’s obstacles in preparing students for storytelling those obstacles are students’ lack of vocabulary and mis-pronunciation, lack of motivation, lack of time, lack of discipline and the challenge to the diversity of students’ personality. Moreover, the solutions to those problems are also presented.